2014
DOI: 10.1021/nn503719n
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Thinning Nanocomposite Hydrogels for the Treatment of Hemorrhage

Abstract: Internal hemorrhaging is a leading cause of death after traumatic injury on the battlefield. Although several surgical approaches such as the use of fibrin glue and tissue adhesive have been commercialized to achieve hemostasis, these approaches are difficult to employ on the battlefield and cannot be used for incompressible wounds. Here, we present shear-thinning nanocomposite hydrogels composed of synthetic silicate nanoplatelets and gelatin as injectable hemostatic agents. These materials are demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
357
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 345 publications
(366 citation statements)
references
References 51 publications
6
357
1
2
Order By: Relevance
“…In a recently published study, LAPONITE® and gelatin nanocomposites were formulated as an injectable hydrogel for hemorrhage treatment. 119 The hydrogel displayed enhanced in vitro and in vivo coagulation properties.…”
Section: Cationic-cm In Pharmaceutical Productsmentioning
confidence: 99%
“…In a recently published study, LAPONITE® and gelatin nanocomposites were formulated as an injectable hydrogel for hemorrhage treatment. 119 The hydrogel displayed enhanced in vitro and in vivo coagulation properties.…”
Section: Cationic-cm In Pharmaceutical Productsmentioning
confidence: 99%
“…[23,24] Some of the promising biomedical applications for nanosilicates-based composites include high-performance elastomers [25][26][27][28], selfhealing structures [29], injectable hemostats [30], moldable hydrogels [31], and drug delivery vehicles [32,33]. Recently, our group showed that by incorporating nanosilicates in collagen-based matrix, significant enhances alkaline phosphate (ALP) activity (an early marker for osteogenesis), and promotes production of mineralized matrix.…”
Section: Introductionmentioning
confidence: 99%
“…16 A range of synthetic and natural polymers such as alginate, gelatin, chitosan, collagen, poly(ethylene glycol) are explored to mimic extracellular matrices. 5, 6 For example, gelatin-based injectable hydrogels have been developed for gene delivery 7 , wound healing 8 , hemostatic agents 8 , stem cell delivery 9 , and tissue engineering 10 . Despite interesting biological characteristics, these injectable hydrogels lack response to external stimuli to control and release entrapped therapeutics.…”
Section: Introductionmentioning
confidence: 99%